+0  
 
0
53
1
avatar+175 

Pre Calc

Given f(x) = x^2−1/ 1−x
and g(x) = x + 2. Find and simplify f(g(2))−g(f(2)).

 Dec 16, 2019
 #1
avatar+106519 
+1

                    x^2  - 1           (x  -1) (x + 1)

f(x)  =         _______  =     ___________    =   - [  x + 1 ]

                       1 - x              -  ( x - 1)

 

f(2)  = - [ 2 + 1 ]=  -3

g(2)  = 2 + 2  = 4

 

So

 

f(g(2))  - g(f(2))  =

 

f ( 4)  - g (-3)  =

 

- [ 4 + 1 ]  - [ -3 + 2]   =

 

- 5  - [ -1 ]  =

 

-4

 

 

 

cool cool cool

 Dec 16, 2019

2 Online Users